2007
DOI: 10.1088/0953-8984/19/37/375108
|View full text |Cite
|
Sign up to set email alerts
|

Second harmonic generation response by gold nanoparticles at the polarized water/2-octanone interface: from dispersed to aggregated particles

Abstract: Gold nanoparticles with a diameter of approximately 20 nm have been observed at the polarized water/2-octanone interface by the nonlinear optical technique of second harmonic generation. Electric field induced adsorption of the gold particles at this liquid/liquid interface is clearly observed and confirms that these are negatively charged. The process is quasi-reversible at high potential sweep rates, but aggregation at the interface is observed at slower sweep rates through the loss of the nonlinear optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…In order to optimize HGN use in SERS based applications it is critical to understand the effect of their structure, size, and aggregation on EM field enhancement. In general, aggregation intensifies the second harmonic generation of HGNs in contact with one another, effectively combining their collective energy to generate new photons with twice the frequency and half the wavelength [292][293][294][295]. HGN aggregates are also known to exhibit both hybridized plasmon modes, which are the result of surface plasmon interactions with cavity plasmon modes, and collective charge transfer resonances [296][297][298].…”
Section: Plasmon Coupling In Aggregates For Sersmentioning
confidence: 99%
“…In order to optimize HGN use in SERS based applications it is critical to understand the effect of their structure, size, and aggregation on EM field enhancement. In general, aggregation intensifies the second harmonic generation of HGNs in contact with one another, effectively combining their collective energy to generate new photons with twice the frequency and half the wavelength [292][293][294][295]. HGN aggregates are also known to exhibit both hybridized plasmon modes, which are the result of surface plasmon interactions with cavity plasmon modes, and collective charge transfer resonances [296][297][298].…”
Section: Plasmon Coupling In Aggregates For Sersmentioning
confidence: 99%
“…Furthermore, fluorescence loss induced by photobleaching and fluorescence recovery after photobleaching on the same system revealed that the lateral diffusion of these assemblies is 4 orders of magnitude slower than its bulk counterpart. 36 Second harmonic generation, 37 surface plasmon resonance 38 and ellipsometry 39 have also been shown as a characterization method for NPs at the LLI. More recently, freezefracture shadow-casting cryo SEM has been performed with single-particle resolution of these assemblies.…”
mentioning
confidence: 99%
“…In general, aggregation intensifies the second harmonic generation of HGNs in contact with one another, effectively combining their collective energy to generate new photons with twice the frequency and half the wavelength [292][293][294][295]. HGN aggregates are also known to exhibit both hybridized plasmon modes, which are the result of surface plasmon interactions with cavity plasmon modes, and collective charge transfer resonances [296][297][298].…”
Section: Plasmon Coupling In Aggregates For Sersmentioning
confidence: 99%